APPLICATION OF OLEANANE AND STERANE INDEX FOR BIOSTRATIGRAPHIC AGE DETERMINATION: EXAMPLES FROM KANGEAN OILS, NORTHEAST JAVA BASIN - Himawan Sutanto; Junita Trivianty Musu (Scientific Contributions Oil and Gas, 2014)
Northeast Java Basin is known as mature Cenozoic basin, yet this understanding override possibility ofsediment older than Cenozoic. This thoughthas brought current exploration strategy of this basin concerningwithin only Cenozoic sediments. Therefore, it is believed that the source rock in this basin was also derivedfrom Cenozoic sediments, especially the Ngimbang Formation, which was formed during Late Eoceneto Early Oligocene in the stage of Early Synrift. On the other hand, the occurrence of Alisporites sp haspointed Cretaceous sediments is a potential source rock. However, it is still debatable due to the presence ofAlisporites similis in Serawak Basin of Malaysia, which is present until Paleocene. Three crude oils from theKangean oil fi eldNortheast Java Basin, namely NEJB-748, NEJB-749 and NEJB-750have been investigatedusing gas chromatography (GC) and gas chromatography/mass spectrometry (GC/MS).Kangean oils areclassifi ed as mixed oil with organic matter originated from marine and terrestrial deposited under oxidizingand reducing conditions. Moreover, Kangean oils show very low oleanane and steraneindexthat may leadus to the conclusion that the oils were originated from Cretaceous source rock.